Enhancing Faba Bean Production through Promoting Integrated Faba Bean Gall Management Practices in Eastern Amhara Region of Ethiopia - Negussie Siyum; Dessalegn Getu; Jhon Hardy Purba; Mesfin Bahta (Agro Bali : Agricultural Journal, 2022)
In Ethiopia, a great variety of diseases affects faba bean production. However, gall forming faba bean new disease has become a very serious disease that seriously affected faba beans producing areas of Wollo. This prescalling up of integrated faba bean gall technology has been conducted at Meket and Wadla woredas of north Wollo in 2017/18 to create wider demand on the management of gall disease and to enhance integrated gall disease management  technology dissemination. The study areas were selected purposively due to high infestation of the disease. A total of 32 farmers were selected based on a voluntary base. Adjacent farms of 5.7 ha at Wadla and 3 ha at Meket was selected and clustered accordingly. Integrated disease management i.e seed dressing with 300 gm Baylaton/100Kg seed, improved varieties and hand weeding were applied as a package for the control of the disease. Dosha with chemical gave an average gain yield of 2.2 tons/ha at Meket whereas Wolki with chemical gave an average grain yield of 2.5 tons/ha at Wadla woreda. However, the local variety with farmers’ practice gave an average grain yield of 100 kg/ha and 900 kg/ha at Wadla and Meket woredas respectively. The result of economic analysis also indicate that the technology is by far advantageous than the local variety and practice. So, the technology should be further disseminated to other hot spot areas of faba bean gall diseases.